Ecosystem services, biodiversity and human wellbeing along climatic gradients in smallholder agro-ecosystems in the Terai Plains of Nepal and Northern Ghana - Thorn, J (2016)
Increasingly unpredictable, extreme and erratic rainfall with higher temperatures threatens to undermine the adaptive capacity of food systems and ecological resilience of smallholder landscapes. Despite growing concern, land managers still lack quantitative techniques to collect empirical data about the potential impact of climatic variability and change. This thesis aims to assess how ecosystem services and function and how this links with biodiversity and human wellbeing in smallholder agro-ecosystems in a changing climate. To this end, rather than relying on scenarios or probabilistic modelling, space was used as a proxy for time to compare states in disparate climatic conditions. Furthermore, an integrated methodological framework to assess ecosystem services at the field and landscape level was developed and operationalised, the results of which can be modelled with measures of wellbeing. Various multidisciplinary analytical tools were utilised, including ecological and socio-economic surveys, biological assessments, participatory open enquiry, and documenting ethnobotanical knowledge. The study was located within monsoon rice farms in the Terai Plains of Nepal, and dry season vegetable farms in Northern Ghana. Sites were selected that are climatically and culturally diverse to enable comparative analysis, with application to broad areas of adaptive planning. The linkages that bring about biophysical and human changes are complex and operate through social, political, economic and demographic drivers, making attribution extremely challenging. Nevertheless, it was demonstrated that within hotter and drier conditions in Ghana long-tongued pollinators and granivores, important for decomposition processes and pollination services, are more abundant in farms. Results further indicated that in cooler and drier conditions in Nepal, the taxonomic diversity of indigenous and close relative plant species growing in and around farms, important for the provisioning of ecosystem services, decreases. All other things equal, in both Nepal and Ghana findings indicate that overall human wellbeing may be adversely effected in hotter conditions, with a potentially significantly lower yields, fewer months of the year in which food is available, higher exposure to natural hazards and crop loss, unemployment, and psychological anxiety. Yet, surveys indicate smallholders continue to maintain a fair diversity of species in and around farms, which may allow them to secure basic necessities from provisioning ecosystem services. Moreover, farmers may employ adaptive strategies such as pooling labour and food sharing more frequently, and may have greater access to communication, technology, and infrastructure. Novel methodological and empirical contributions of this research offer predictive insights that could inform innovations in climate-smart agricultural practice and planning.